Perception of primary care nurses about mental health actions: An integrative review (Research, Society and Development, 2021)
Introduction: Mental health is considered one of the serious global health problems, mental illness is not only linked to the psychic suffering of the individual, but to the entire group that is part of his environment, in this context Primary Health Care (PHC), becomes the first gateway to these individuals, being perhaps the first contact of the user to the health care network. Objective: to analyze, based on literature, mental health actions by nurses in Primary Health Care. Methodology: this is a descriptive study with a qualitative approach of integrative review. To achieve this goal, it was initially carried out at the Virtual Health Library (VHL), followed in the following LILACS, BDENF and MEDLINE databases, having as keywords, Mental Health; Primary Health Care; Nursing Care, associated through the Boolean operator AND. Results: It was observed that the selected studies obtained satisfactory results, with practical evidence on the perception of primary care nurses about mental health actions, thus three categories were used in the discussion to better explain the results: Nurses' perception of the concept and mental health care, Mental health actions in primary care and challenges of nursing professionals in mental health actions. Conclusion: This way we see the need for permanent education of these professionals, so that there are changes in the way of assisting users in mental suffering, considering that knowledge is the foundation for breaking barriers and social stigmas that surround health care mental.